PELAYANAN BIMBINGAN DAN KONSELING ISLAM (STUDI KASUS PELAYANAN KLINIK VCT RUMAH SAKIT ISLAM SULTAN AGUNG SEMARANG DALAM MENINGKATKAN KESEHATAN MENTAL PASIEN HIV/AIDS) - Aristiana, Noor Fuat; Bukhori, Baidi; Hasanah, Hasyim (Da'wa and Communication Faculty State Islamic University Walisongo, Semarang, Indonesia, 2015)
This research is quantitative research to describe mental hygiene problems and to analyze islamic guidance and counseling to increase the healthiness of patient with HIV in VCT Clinic, Sultan Agung Hospital Semarang. The source of data in this research is counselor and patient with HIV. The method of collecting data use interview, observation, and documentation. The method analyze is interacive analyze model. The outcame from the research shows that, fisrt patient with HIV/AIDS have a mental hygiene problems. Second, islamic guidance and counseling services for them consist of pre test counseling, pasca test counseling, and sustainable counseling. Third, islamic guidance and counseling services to increase mental hygiene patient with HIV/AIDS focused on sefl-acceptance. To increase mental hygiene patient with HIV/AIDS required sustainable accompaniment about development and empowerment of the patient potential and family with HIV/AIDS***Penelitian ini merupakan penelitian kualitatif yang bertujuan untuk mendiskripsikan problem kesehatan mental dan menganalisis pelayanan bimbingan dan konseling Islam dalam meningkatkan kesehatan mental pasien HIV/AIDS di Klinik VCT Rumah Sakit Islam Sultan Agung Semarang. Sumber data adalah konselor dan pasien HIV/AIDS. Metode pengumpulan data wawancara, observasi, dan dokumentasi. Metode analisis data model analisis interaktif. Hasil penelitian menunjukkan, pertama pasien HIV/AIDS memiliki problem kesehatan mental. Kedua, pelayanan bimbingan dan konseling Islam bagi penderita HIV/AIDS terdiri dari konseling pra tes, konseling pasca tes, dan konseling berkelanjutan. Ketiga, pelayanan bimbingan dan konseling Islam dalam meningkatkan kesehatan mental pasien HIV/AIDS ditekankan pada penerimaan diri.Untuk meningkatkan kesehatan mental pada diri pasien diperlukan pendampingan lanjutan tentang pengembangan dan pemberdayaan potensi korban dan keluarga dengan HIV/AIDS